Frequency Of Perinatal Outcome Inpatients With Umbilical Cord Prolapse - Asma, Asma; Shaikh, Khushboo; Tooba, Tooba; Haleema, Haleema; Waheeda, Waheeda; Beenish, Beenish (Journal of Neonatal Surgery, 2025)
Introduction: Umbilical cord prolapse (UCP) is an uncommon but potentially fatal obstetric emergency. Several risk factors for UCP have been identified. The first step in anticipating this obstetric emergency and decreasing the perinatal morbidity and mortality. Umbilical cord prolapse among pregnant women is an emergency and potentially dangerous condition, which may lead to grave consequences regarding fetal outcomes, if not properly managed. This study is designed to determine the fetal outcome among these patients, as it may help us to anticipate and educate our patients better. Objectives: To determine the frequency of perinatal outcomes among patients having umbilical cord prolapse. Design: Cross-sectional study Setting: Gynecology & Obstetrics Department, Sheikh Zayed Women Hospital, Larkana. Duration of Study: 6-months from 01-04-2020 to 30-09-2020. Subject and Methods: Eighty two patients having umbilical cord prolapse (UCP) presenting in labour room were recruited in this study. Their demographic details including age, gestational age, parity, previous history of UCP and history of polyhydramnios was obtained. They was assessed for perinatal outcome and all the data was entered on the proforma (Attached). Results: - The average age of the women was 26.52±5.17 years. Frequency of perinatal outcomes among patients having umbilical cord prolapse are listed in table 2. Cesarean sectionwas performed in 68.3% (56/82), preterm delivery was found as 48.8% (40/82), mortality as 18.3% (18/82), Apgar score 27 at 1 minute as 54.9% (45/82) and Apgar score 27 at 5 minute as 82.9% (68/82) in a study. Conclusion: Umbilical cord prolapse is associated with a significant perinatal mortality in this study, especially in those with spontaneous rupture of membranes that occurred outside the hospital setting...